TEACHERS’ STRATEGIES IN HANDLING STUDENTS' ANXIETY IN ENGLISH SPEAKING CLASS - Rimtahi Marbun; Elan Nurroctavia Purba; Calvyn Siregar; Dumaris E Silalahi (JEELL (Journal of English Education, Linguistics and Literature), 2026)
Speaking is a challenging skill for EFL students, with anxiety often hindering their participation and language development. This article explores teacher strategies for managing speaking anxiety in English-speaking classrooms. Using a systematic literature review (SLR) of studies published between 2015 and 2025, the research identifies key causes of anxiety, including fear of negative evaluation and lack of preparation. The review also examines the significant impact of anxiety on students' speaking performance, participation, and motivation. Effective strategies, such as creating a supportive classroom environment, providing constructive feedback, and offering ample practice opportunities, are discussed. The findings underscore the vital role of teachers in reducing anxiety and fostering an environment conducive to language learning.